Advancing the agency of adolescent girls - Edmonds, Eric; Feigenberg, Ben; Leight, Jessica (MIT Press, 2023)
More than 98 million adolescent girls are not in school. Can girls influence their schooling without changes in their family's economic environment? In Rajasthan, India, we examine the impact of a school-based life skills program that seeks to address low aspirations, narrow societal roles for girls and women, restricted networks of social support, and limited decision-making power. We find the intervention causes a 25% decline in school dropout that persists from seventh grade through the transition to high school. Improvements in socioemotional support among girls exposed to the intervention seem especially important in their decision to stay in school.